A short-term study of the net phytoplankton in Sapian Bay - Hermosa, Lea Cornelio (Iloilo College of Fisheries, University of the Philippines, 1992)
The composition and distribution of the net phytoplankton in Sapian Bay, Capiz was investigated in three stations and in the surface and bottom layers of the water over the period 27 April 1989 to 07 September 1989.. Water samples for the biological and physico-chemical analyses were collected using a reversing Nansen bottle. Phytoplankton samples were concentrated with a 47 um plankton net. Quantitative analyses were done using a Sedgewick-Rafter counting chamber. An inverted microscope was used to view and identify the phytoplankton component. A total of 63 genera were identified of which 51 were diatoms, 5 dinoflagellates, 7 green algae, and one blue-green algae. Diatoms and dinoflagellates were found to be the most abundant groups. Peridinium dominated the phytoplankton assemblage in April ;Chaetoceros in May; Asterionella in June ; Bacteriastrum and Rhizosolenia co-dominated in July ; Chaotoceros in August ; and Nitzschia in September. The various species of Ceratium, Eucampia, Surirella, Pleurosigma, and Ditylium, among others, reached important numbers as well. Species diversity ranged from 0.110 to 2.970 while evenness values ranged from 0.100 to 2.230. Phytoplankton density ranged from 285 to 50,767 organism/1. A Principal Components Analyses (PCA) of phytoplankton diversity and selected physic-chemical and meteorologic variables yielded a 25.44% variability contributed by PC 1 with the total variance strongly influenced by wind velocity, rainfall, salinity, phytoplankton diversity, prevailing wind direction, and nitrate. The closeness of the values of salinity and phytoplankton diversity suggests strong correlation with these variables and that diversity seemed to be strongly influenced by salinity.
Thesis (M. S. Fisheries) - University of the Philippines in the Visayas, April 1992.
Keywords: Net phytoplankton; Sapian Bay; Phytoplankton